National Political Elites, European Integration and the Eurozone Crisis - Mihail Chiru (Journal of Contemporary European Research, 2019)
The book draws on surveys of national legislators to analyze whether and how has the economic crisis changed the elites' levels of identification with the European Union, their perceptions of the functioning of the EU and their preferences for further integration and the future of the EU.